Integral of Polynomial Series

Calculus Level 5

Evaluate 0 ( x 3 2 x 5 + 2 x 7 4 3 x 9 + 2 3 x 11 4 15 x 13 + ) d x . \int_0^\infty\left(x^3-2x^5+2x^7-\frac{4}{3}x^9+\frac{2}{3}x^{11}-\frac{4}{15}x^{13}+\cdots\right)dx. Hint : Use Maclaurin series for exponential function.


The answer is 0.125.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Aug 30, 2018

Relevant wiki: Gamma Function

The integral can be written into:

I = 0 x 3 n = 0 ( 2 x 2 ) n n ! d x = 0 x 3 e 2 x 2 d x Let u = x 2 d u = 2 x d x = 1 2 0 u e 2 u d u Let t = 2 u d t = 2 d u = 1 8 0 t 2 1 e t d t Gamma function Γ ( z ) = 0 t z 1 e t d t = Γ ( 2 ) 8 = 1 ! 8 Since Γ ( n ) = ( n 1 ) ! = 1 8 = 0.125 \begin{aligned} I & = \int_0^\infty x^3 \sum_{n=0}^\infty \frac {(-2x^2)^n}{n!} dx \\ & = \int_0^\infty x^3 e^{-2x^2} dx & \small \color{#3D99F6} \text{Let }u = x^2 \implies du = 2x \ dx \\ & = \frac 12 \int_0^\infty u e^{-2u} du & \small \color{#3D99F6} \text{Let } t = 2u \implies dt = 2 \ du \\ & = \frac 18 \int_0^\infty t^{2-1} e^{-t} dt & \small \color{#3D99F6} \text{Gamma function }\Gamma (z) = \int_0^\infty t^{z-1}e^{-t} dt \\ & = \frac {\Gamma (2)}8 = \frac {1!}8 & \small \color{#3D99F6} \text{Since }\Gamma (n) = (n-1)! \\ & = \frac 18 = \boxed{0.125} \end{aligned}

How do we know that the given series is not the MacLaurin series of x 3 e x 12 2 x 2 x^3e^{\large -x^{12} - 2x^2} , which yields a different answer?

Jesse Nieminen - 2 years, 9 months ago

Log in to reply

Why is it x 3 e x 12 2 x 2 x^3e^{-x^{12}-2x^2} ?

x 3 e x 12 2 x 2 = x 3 ( 1 x 12 + x 24 2 + ) ( 1 2 x 2 + 4 x 4 2 + ) x^3e^{-x^{12}-2x^2} = x^3\left(1- x^{12} + \dfrac {x^{24}}2 + \cdots \right)\left(1- 2x^{2} + \dfrac {4x^{4}}2 + \cdots \right)

Chew-Seong Cheong - 2 years, 9 months ago

Log in to reply

Yes, as you can see from the factorization, the middle factor doesn't affect the visible part of the series given in this problem, showing that the answer isn't unique, even with the hint.

Of course, obviously the simplest function yielding the given series is x 3 e 2 x 2 x^3 e^{-2x^2} , but it is not the only valid answer.

Jesse Nieminen - 2 years, 9 months ago
Brian Moehring
Aug 29, 2018

At some level, we have to simply guess what the given power series is, so the first step in the solution is rather unsatisfying: We just have to note that x 3 e 2 x 2 = n = 0 ( 1 ) n 2 n n ! x 3 + 2 n = x 3 2 x 5 + 2 x 7 4 3 x 9 + 2 3 x 11 4 15 x 13 + x^3e^{-2x^2} = \sum_{n=0}^\infty \frac{(-1)^n \cdot 2^n}{n!} x^{3+2n} = x^3 - 2x^5 + 2x^7 - \frac{4}{3}x^9 + \frac{2}{3}x^{11} - \frac{4}{15}x^{13} + \cdots

That is, we need to evaluate 0 x 3 e 2 x 2 d x \int_0^\infty x^3e^{-2x^2}\,dx To do this, use the substitution u = 2 x 2 u=2x^2 to rewrite it as 1 8 0 u e u d u = 1 8 [ ( u + 1 ) e u ] 0 = 1 8 = 0.125 \frac{1}{8} \int_0^\infty u e^{-u}\,du = \frac{1}{8} \Big[-(u+1)e^{-u}\Big]_0^\infty = \frac{1}{8} = \boxed{0.125}

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...